Analisis Teoritis Perhitungan High Heating Value (HHV) Bio-Coal Berbahan Dasar Tandan Kosong Kelapa Sawit - Khotimah, Nur; martin, Awaludin (Universitas Muhammadiyah Metro, 2023)
Oil palm empty fruit bunches can be used as a renewable energy source made into bio-coal through the torefaction process. The combustion value of oil palm empty fruit bunches is expressed in terms of heating value to indicate the amount of energy obtained. The heating value is also known as the heat value of the fuel, which is one of the important parameters for fuel quality. This study aims to calculate the high heating value of bio-coal theoretically and compare it with experimental results. High heating value is calculated based on the enthalpy of combustion (hC), which indicates the amount of energy released during the combustion process when the fuel is completely burned at a certain temperature and pressure. In other words, the heating value of the fuel is equal to the absolute value of the enthalpy of combustion of the fuel. The theoretical calculation results are different or smaller than the experimental data. Experimentally the high heating value with a sample weight of 0.25 kg, 0.5 kg and 1 kg is 20334 kJ/kg, 23578 kJ/kg, 26346 kJ/kg respectively, while the theoretical high heating value for sample weight 0.25 kg, 0.5 kg and 1 kg respectively amounted to 22053.60 kJ/kg, 22751.66 kJ/kg, 24147.69 kJ/kg. Variability in biomass composition such as chemical elements or components, moisture content, particle size, and volatile matter content can have a significant effect on combustion value